JACQUES RANCIÈRE AND THE PROBLEM OF WHEN “POLITICS EXISTS”. EQUALITY AS FOUNDATION AND ITS (DE)POLITICIZING CONSEQUENCES - Gambarotta, Emiliano (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2017)
Under what conditions politics exists? This question lies beneath the whole Rancière’s theory. While according to him politics does not always exist, domination is what exists instead, a police division of the sensible. The main purpose of this paper is to grasp these conditions and what they say to us about this political theory. To this end, I will do a internal reading of such theory, looking into the inner logic of Rancière’s materials, with the attempt of understanding not only its potentialities but also the blind spots by  problematizing the politics. Briefly, I aim to accomplish an “immanent critique” of his theory, focused in how the author conceives the relation between knowledge and politics. Thus, I will first study those factors that lead knowledge (philosophical, sociological, etc.) to suppress politics, and the dispute that characterize it, according to Rancière. This will lead me to detail which are the conditions he pointed as necessary for “politics exists”. Then, I will analyze the status assigned to the notion of “equality” in this theory, since separate it from all pretension of (cognitive) truth is a key element in Rancière’s objections to the knowledge and politics relation, being this, at the same time, one of the most radical contemporary questionings of such relation. The goal of this immanent critique of the theory is to elaborate the elements for a new discussion of the link between knowledge and politics, particularly about the place that the critical knowledge can have in a democratic politics.